Women’s public office positions in Islāmic jurisprudence: the case of Malaysia - Abdul Karim, Asar; Ghalia, Bouhedda; Ab Hamid, Mohd Rashid (2015)
The disagreement opinions among Muslim scholars about permissibility for women to hold public office positions seem to be a never ending episode. The issue has been raised by Muslims all over the world, whereby the root cause is actually related to the misunderstanding of Muslim scholars about some controversial nuṣūṣ which related to the issue. Therefore, the objective of the study is to examine the reality of those arguments made by the Muslim scholars and the subsequent effects in the issue of fatwas by the scholars pertaining to the matter. The study also will include the finding data collected from a sample of 369 Malaysian Muslims respondents who met certain criteria set by the study conducted by the researchers; results of the study show several significant findings. The most important finding is the majority of respondents agreed that women can hold some public office positions, but not all the positions. The findings therefore will help to address the issue more appropriately and plan for better educational programs.